2020
DOI: 10.1055/s-0040-1714761
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Chelating Solutions in the Resistance of Glass Fiber Posts to the Root Dentin

Abstract: Objective To evaluate the influence of chelating agents (EDTA, citric acid and Tetraclean) on glass fiber posts adhesion to root dentin. Materials and Methods Forty mandibular premolars single canals, with complete apical root, straight, circular cross sections were selected, accessed and had the cervical third prepared with Gates-Glidden drills, then included in resin, instrumented with ProTaper Universal and the root canal obturation was carried out. After, the samples were randomly divided into 4 groups (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…At the end, 13 articles ( 10 , 12 - 23 ) were selected for the analysis of the full text. At this stage, 5 articles were excluded for the following reasons: 3 articles ( 10 , 12 , 13 ) because the irrigating variable was only applied in the preparation of the space for a post, and not in the chemical-mechanical preparation of endodontic treatment; one ( 14 ) for not having assessed the adhesion of post; and 1 ( 15 ) because it was not possible to access the text completely, either through the magazine or through contact with the authors. Finally, 8 articles were included ( 16 - 23 ) in the systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…At the end, 13 articles ( 10 , 12 - 23 ) were selected for the analysis of the full text. At this stage, 5 articles were excluded for the following reasons: 3 articles ( 10 , 12 , 13 ) because the irrigating variable was only applied in the preparation of the space for a post, and not in the chemical-mechanical preparation of endodontic treatment; one ( 14 ) for not having assessed the adhesion of post; and 1 ( 15 ) because it was not possible to access the text completely, either through the magazine or through contact with the authors. Finally, 8 articles were included ( 16 - 23 ) in the systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…Conditioning solutions, such as irrigating solutions in the endodontic treatment [13], induce morphological changes in the intra-radicular dentin through alterations in both superficial porosity and the diameter of the dentinal tubules [32]. These processes induce modification at collagen fibers of the dentinal wall; it also affects the calcium/phosphate ratio of the inorganic layer in the dentin, conditioning monomer penetration into the demineralized dentin [12]. These modifications can affect dentin hybridization by reducing the post-endodontic adhesive interface [13], provoking changes in adhesive system impregnation patterns, and reducing the infiltration into peritubular dentin resulting in restoration challenges for clinicians [14,33].…”
Section: Conditioning Solutionsmentioning
confidence: 99%
“…This technique consists of energy released by the instrument, which leads to an improvement in the physicochemical properties of the irrigation solution as a result of the agitation, the transmission of acoustic waves, and formation of bubbles due to the cavitation phenomena, which detonates and produces temperature increasing and whose pressure results in shock waves against the root canal wall [23,58]. The SSL removal process occurs through the continuous flow of the irrigation solution, which promotes efficient cleaning of the debris inside the root canal [12]. Interestingly, using SEM indicated that irrigation with 17% EDTA for 15 s with ultrasonic activation and subsequent etching with phosphoric acid 37% liquid with ultrasonic activation improves the SSL removal from the root canal compared with other irrigant solutions such as EDTA alone, 37% orthophosphoric acid, or EDTA + 37% orthophosphoric a without activation [16].…”
Section: Passive Ultrasonic Irrigationmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Marques et al shown that NaOCl alone may have oxidizing effect that might decrease bond strength. 17 Sodium ascorbate is a sodium salt of ascorbic acid and well known as effective antioxidant that could reverse the compromising effect of NaOCl on bond strength to enamel and dentin. Celik et al claimed that Sodium ascorbate application after NaOCl conventional syringe irrigation improved the bond strength value.…”
Section: Background and Rationalementioning
confidence: 99%